Longitudinal changes in moderate‐to‐vigorous‐intensity physical activity in children and adolescents: A systematic review and meta‐analysis. (23rd October 2019) - Farooq, Abdulaziz; Martin, Anne; Janssen, Xanne; Wilson, Mathew G.; Gibson, Ann‐Marie; Hughes, Adrienne; Reilly, John J.
Summary: Moderate‐to‐vigorous‐intensity physical activity (MVPA) is important for childhood obesity prevention and treatment, yet declines with age. Timing and magnitude of the decline in MVPA in children and adolescents are unclear but important for informing effective obesity intervention development. This systematic review aimed to determine and compare the year‐to‐year changes in MVPA among children and adolescents. Longitudinal studies were identified by searching 10 relevant databases up to December 2018. Studies were eligible for inclusion if they reported accelerometer‐assessed MVPA (min day −1 ) separately for boys and girls and had follow‐up duration of at least 1 year. After screening 9, 232 studies, 52 were included representing 22, 091 aged 3 to 18 year olds (boys=8, 857; girls=13, 234). Pooled‐analysis of the relative change in MVPA per year showed a decline of −3.4% (95% CI, −5.9 to −0.9) in boys and −5.3% (95% CI, −7.6 to −3.1) in girls, across all age groups. There were notable declines in MVPA at age 9 for both boys (−7.8%, 95% CI, −11.2 to −4.4) and girls (−10.2%, 95% CI, −14.2 to −6.3). The relative decline in MVPA affects both sexes from an early age; however, it is greater among girls. Interventions to promote MVPA should start before adolescence.